2018
DOI: 10.14236/ewic/hci2018.129
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Designing Chatbots in Mental Healthcare – A Case Study on iHelpr

Abstract: This paper outlines the design and development of a chatbot called iHelpr for mental healthcare that 1) administers self-assessment instruments/scales, 2) provides wellbeing and self-help guidance and information, all within a conversational interface. Chatbots are becoming more prevalent in our daily lives, with bots available to provide the user with daily weather forecasts, book holidays, and even converse with a virtual therapist. It is predicted that users may soon prefer to complete tasks using a convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 9 publications
0
16
0
2
Order By: Relevance
“…Usability questionnaires are discussed, and adapted to create a usability test to assess the iHelpr chatbot. This paper is a continuation of previous work completed in the area of chatbots for mental health care [5][6][7].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Usability questionnaires are discussed, and adapted to create a usability test to assess the iHelpr chatbot. This paper is a continuation of previous work completed in the area of chatbots for mental health care [5][6][7].…”
Section: Introductionmentioning
confidence: 79%
“…In previous works [5][6][7], Inspire Workplaces developed a chatbot, iHelpr, in partnership with Ulster University through a Knowledge Transfer Partnership. Inspire Workplaces provide programmes and wellbeing solutions for private and public sector organisations, and educational institutions across the island of Ireland.…”
Section: Inspire Support Hub and Ihelprmentioning
confidence: 99%
“…In response to growing waiting lists and difficulties in accessing mental health services, Cameron et al (2018) developed iHelpr, a self-help mental health chatbot. It is suggested that conversational interfaces may soon replace web pages and smartphone apps as the preferred means of conducting online tasks [8]. Chatbots are suggested to be of use in the area of mental health because they provide instant access to help and support and increased efficiency [6].…”
Section: Chatbots In Healthcarementioning
confidence: 99%
“…Mulvenna et al [102] present a manifesto with 12 principles as a starting point for ethical by design development of chatbots for mental health, which they have used to develop the iHelpr system [103]. These include among others empathy for users, providing informed decisions, respect to choose ways to be engaged, privacy and security, equitable access and complementary viewpoints, challenge possible biased incorporated into the system, support through lifespan and progression policy, planning for failure, transparency and reporting.…”
Section: Ethical Issuesmentioning
confidence: 99%